Monitoring of minimal residual disease in acute myeloid leukemia with frequent and rare patient-specific NPM1 mutations - Dvorakova, Dana; Racil, Zdenek; Jeziskova, Ivana; Palasek, Ivo; Protivankova, Marketa; Lengerova, Martina; Razga, Filip; Mayer, Jiri (American journal of hematology, 2010)
Nucleophosmin (NPM1) mutations in exon 12 are the most common genetic alternation in cytogenetically normal AML (CN-AML). Although mutation types A, B, and D represent the majority of cases, rare mutation variants of the NPM1 gene in individual patients do occur. In this study, we have evaluated a novel, DNA-based real-time quantitative polymerase chain reaction (RQ-PCR) for the detection of three of the most commonly occurring mutations and for six rare patient-specific mutation types, which represent 28% of all of the NPM1 mutations in our group of 25 CN-AML patients. Furthermore, the prognostic relevance of NPM1-based monitoring of minimal residual disease (MRD) in peripheral blood (PB), bone marrow (BM), and in specific cell subsets (CD34(+), CD34(-), CD34(dim)) of BM were evaluated. In 80% of the evaluable patients, a molecular relapse preceded a hematological relapse. Moreover, in this subset of patients, the molecular relapse occurred at a median of 97 days before the hematological relapse. Our compartment analysis showed a strong correlation between BM and PB (r = 0.907, P < 0.001) as well as a high copy number of mutated NPM1 in CD34(+) BM cells. In conclusion, we have demonstrated applicability of our presented RQ-PCR method for a large percentage of mutated NPM1 patients with CN-AML as well as the usefulness for long-term follow-up monitoring of MRD and the prediction of hematological relapse.
Keywords: mutace; dospělí; Neoplasm, Residual; Nuclear Proteins; krevní buňky; Recurrence; Female; jaderné proteiny; Adult; ženské pohlaví; mutační analýza DNA; Antigens, CD34; Gene Dosage; Predictive Value of Tests; buňky kostní dřeně; antigeny CD34; prediktivní hodnota testů; lidé; recidiva; reziduální nádor; nukleofosmin; DNA Mutational Analysis; Mutation; prognóza; Male; Nucleophosmin; Aged; akutní myeloidní leukemie; Bone Marrow Cells; Prognosis; lidé středního věku; Blood Cells; senioři; mužské pohlaví; genová dávka; Middle Aged; Leukemia, Myeloid, Acute; Humans